2023
DOI: 10.3390/nu15163623
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Chronic Diseases and Acute Infections with Vitamin D Sufficiency

Sunil J. Wimalawansa

Abstract: Apart from developmental disabilities, the prevalence of chronic diseases increases with age especially in those with co-morbidities: vitamin D deficiency plays a major role in it. Whether vitamin D deficiency initiates and/or aggravates chronic diseases or vice versa is unclear. It adversely affects all body systems but can be eliminated using proper doses of vitamin D supplementation and/or safe daily sun exposure. Maintaining the population serum 25(OH)D concentration above 40 ng/mL (i.e., sufficiency) ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 158 publications
(251 reference statements)
0
8
0
1
Order By: Relevance
“…Figure 2 illustrates fundamental differences between the hormonal and non-hormonal forms of calcitriol and the related generation of calcitriol. demonstrates key functional differences between the circulatory hormonal form of calcitriol (the hormonal form) that is generated in renal tubular cells vs. the intracellularly generated calcitriol in peripheral target cells, such as immune cells (modified from Wimalawansa, SJ., 2023 [7]).…”
Section: Non-classical Actions Of Calcitriolmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 illustrates fundamental differences between the hormonal and non-hormonal forms of calcitriol and the related generation of calcitriol. demonstrates key functional differences between the circulatory hormonal form of calcitriol (the hormonal form) that is generated in renal tubular cells vs. the intracellularly generated calcitriol in peripheral target cells, such as immune cells (modified from Wimalawansa, SJ., 2023 [7]).…”
Section: Non-classical Actions Of Calcitriolmentioning
confidence: 99%
“…Elevated PTH levels resulting from low dietary calcium or, more commonly, vitamin D deficiency contribute to heightened bone turnover and gradual loss of bone mineral demonstrates key functional differences between the circulatory hormonal form of calcitriol (the hormonal form) that is generated in renal tubular cells vs. the intracellularly generated calcitriol in peripheral target cells, such as immune cells (modified from Wimalawansa, SJ., 2023 [7]).…”
Section: Genetic Influences On Vitamin D/ctrmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ultraviolet (UV) radiation-activated cutaneous synthesis is considered the main source of vitamin D. Cutaneously generated pre-vitamin D gets converted to vitamin D 3 via thermal isomerization and enters the blood circulation bound to vitamin D binding protein [2,3]. Once in the circulation, vitamin D is hydroxylated into 25hydroxyvitamin D [25(OH)D; calcidiol] in the liver, and then in the kidney to 1,25-dihydroxyvitamin D [1,25(OH) 2 D; calcitriol], the physiologically active form of vitamin D [4]. Calcitriol can also be generated within peripheral target cells, functioning as a localized cytokine and a signaling molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an observational study indicated that circulating vitamin C levels have a protective effect against cholesterol gallstones ( 18 ). Notably, vitamin D exerts potent regulatory effects on both innate and adaptive immunity ( 19 ), with research suggesting that maintaining serum 25(OH)D concentrations above 40 ng/mL can significantly reduce symptomatic diseases and decrease the prevalence of infections and chronic conditions ( 20 ).…”
Section: Introductionmentioning
confidence: 99%